2012
DOI: 10.1179/2046904712z.00000000048
|View full text |Cite
|
Sign up to set email alerts
|

The dengue situation in Africa

Abstract: Dengue outbreaks and epidemics have been reported in all regions of Africa, and it is believed that all four dengue virus serotypes are in circulation. Available data suggest that dengue is endemic to 34 African countries and that Aedes aegypti mosquitoes – the primary vector for dengue transmission – are known to be present in all but five countries. Whether populations in Africa are susceptible to dengue at the same rates as in Asia and Latin America is difficult to determine from the available data. Several… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
106
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(115 citation statements)
references
References 14 publications
6
106
0
3
Order By: Relevance
“…Epidemiological studies in these countries are scarce. Dengue infection had been reported in Equatorial Guinea previously, 13 but to our knowledge no studies have been conducted in this country. In Nigeria, a recent report carried out on 310 febrile patients showed a 67.7% seroprevalence of dengue using plaque reduction neutralization testing to rule out cross-reactivity.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Epidemiological studies in these countries are scarce. Dengue infection had been reported in Equatorial Guinea previously, 13 but to our knowledge no studies have been conducted in this country. In Nigeria, a recent report carried out on 310 febrile patients showed a 67.7% seroprevalence of dengue using plaque reduction neutralization testing to rule out cross-reactivity.…”
Section: Discussionmentioning
confidence: 89%
“…Although several outbreaks have been reported in this continent and the number of epidemiological studies has increased in recent years, studies are still scarce. 13,14 Therefore, there is a need to collect epidemiological data on dengue infection in Africa to uncover the probably large hidden African dengue burden and its extension within this continent. 15 In our study, we found the highest rate of diagnosed cases in patients who had visited Asia (9%), followed by those traveling from Latin America and the Caribbean (6.1%) and, very close behind, from Africa (4.5%).…”
Section: Discussionmentioning
confidence: 99%
“…Even though published reports are scarce, dengue has been documented in at least 34 countries in Africa ( 2 ). The role of travelers as sentinels of infectious disease has proven to be invaluable in this regard; dengue in returning travelers was the only evidence for local DENV transmission for 12 of these countries.…”
mentioning
confidence: 99%
“…Effectively, epidemics may remain undetected until diagnosis is assessed in another country from a returning infected visitor. Moreover, travelers may be more susceptible to dengue infection than locals, particularly travelers from non-endemic to endemic areas [8]. Dengue is also under recognized in Africa because of low awareness by health care providers, other prevalent febrile illnesses, and lack of diagnostic testing and systematic surveillance [9].…”
Section: Introductionmentioning
confidence: 99%
“…Dengue virus is still expanding worldwide to new territories with the first epidemic in Cape Verde in 2009 with more than 17,000 cases [7]. It is likely that all four subtypes of the dengue virus are present but the lack of formal laboratory testing or surveillance initiatives means that it is difficult to verify this [8].…”
Section: Introductionmentioning
confidence: 99%